ANALISA PENERAPAN PRINSIP GOOD COORPORATE GOVERNANCE (GCG) STUDI KASUS PADA SEKOLAH TINGGI TEKNOLOGI MIGAS BALIKPAPAN - Lukman Lukman (Sekolah Tinggi Teknologi MIGAS, 2021)
Good Corporate Governance (World Bank) (Tangkilisan; 2003) is a collection of laws, regulations and rules that must be fulfilled that can encourage the performance of company resources to work efficiently, resulting in long-term sustainable economic value for shareholders and the surrounding community. overall. Then according to Zarkashi (2008). Good Corporate Governance (GCG) is a structure used by stakeholders, shareholders, commissioners and managers to formulate company goals and means to achieve company goals, as well as a means to achieve these goals and monitor performance. There are five principles for Good Corporate Governance in Indonesia: transparency, accountability, responsibility, independency, and fairness. content analysis, which is a method of collecting research data through observation and analysis techniques of the content or message of a document (including: advertisements, reports, employment contracts, journals, magazines, or newspapers. The purpose of content analysis is to identify the characteristics or specific information contained in a document to produce an objective and systematic description (Bambang, 1999).